THE IMPORTANCE OF INTERCULTURAL COMPETENCE FOR TEACHING INTERNATIONAL STUDENTS - Yakubov Zafar Kudratovich (Scholar Express Journals, 2025)
As globalization continues to influence higher education, the presence of international students in schools and universities worldwide is rapidly increasing. This demographic shift has brought both opportunities and challenges to educators, particularly in understanding how to create inclusive and effective learning environments. Intercultural competence—the ability to interact effectively and appropriately with people from different cultural backgrounds—has emerged as a critical skill for teachers. This article explores the role of intercultural competence in teaching international students, reviews the current literature, analyzes practical strategies and outcomes, and emphasizes the need for culturally responsive pedagogy in a globalized educational context
Keywords: Intercultural competence; international students; global education